An Experimental Study and Modeling on the Thermo‐Rheological Properties of Polyurethane‐Based Magnetorheological Gel. Issue 8 (3rd February 2023) - Zhang, Guang; Chen, Junyu; Zhang, Jinning; Zhang, Zheng; Sun, Min; Yu, Yang; Wang, Jiong
Abstract : Magnetorheological (MR) gel is a novel type of smart material with field‐dependent rheological properties, which is mainly composited of soft magnetic particles and a gel‐like matrix. Its controllable rheological behaviors depend on many factors, in which temperature is a significant factor requiring further study. Herein, polyurethane‐based MR gel with a 60% weight fraction of carbonyl iron is developed. The influence of temperature on the rheological characteristics of the MR gel sample is systematically investigated. The steady shear test is adopted to determine the yield stress and dynamic viscosity of MR gel under different temperatures. A new stress model based on Bingham constitutive model and Arrhenius relation is proposed to incorporate the influence of the temperature and to capture the hysteresis characteristics and strain stiffening properties. The results show that yield stress shows exponential decay with temperature and at the same time, dynamic viscosity displays exponential decay both along with temperature and current. Finally, hysteresis behavior responses by sinusoidal strain excitation with the frequency of 0.1, 5, and 15 Hz at the fixed amplitude of 50% and current of 2 A have been extracted to analyze the impact of temperature on the damping and stiffness properties of the MR gel. Abstract : Herein, polyurethane‐based magnetorheological (MR) gel with a 60% weight fraction of carbonyl iron is developed. The influence of temperature on rheological characteristics of MR gel sample is systematically investigated. And a new model based on Bingham model and Arrhenius relation is proposed to incorporate the influence of the temperature and to capture the hysteresis characteristics and strain stiffening properties.